Dopamine D2 Antagonist-Induced Striatal Nur77 Expression Requires Activation of mGlu5 Receptors by Cortical Afferents - Maheux, Jérôme; St-Hilaire, Michel; Voyer, David; Tirotta, Emanuele; Borrelli, Emiliana; Rouillard, Claude; Rompré, Pierre-Paul; Lévesque, Daniel (Frontiers in Pharmacology, 2012)
Dopamine D2 receptor antagonists modulate gene transcription in the striatum. However, the molecular mechanism underlying this effect remains elusive. Here we used the expression of Nur77, a transcription factor of the orphan nuclear receptor family, as readout to explore the role of dopamine, glutamate and adenosine receptors in the effect of a dopamine D2 antagonist in the striatum. First, we investigated D2 antagonist-induced Nur77 mRNA in D2L receptor knockout mice. Surprisingly, deletion of the D2L receptor isoform did not reduce eticlopride-induced upregulation of Nur77 mRNA levels in the striatum. Next, we tested if an ibotenic acid-induced cortical lesion could block the effect of eticlopride on Nur77 expression. Cortical lesions strongly reduced eticlopride-induced striatal upregulation of Nur77 mRNA. Then, we investigated if glutamatergic neurotransmission could modulate eticlopride-induced Nur77 expression. A combination of a metabotropic glutamate type 5 (mGlu5) and adenosine A2A receptor antagonists abolished eticlopride-induced upregulation of Nur77 mRNA levels in the striatum. Direct modulation of Nur77 expression by striatal glutamate and adenosine receptors was confirmed using corticostriatal organotypic cultures. Taken together, these results indicate that blockade of postsynaptic D2 receptors is not sufficient to trigger striatal transcriptional activity and that interaction with corticostriatal presynaptic D2 receptors and subsequent activation of postsynaptic glutamate and adenosine receptors in the striatum is required. Thus, these results uncover an unappreciated role of presynaptic D2 heteroreceptors and support a prominent role of glutamate in the effect of D2 antagonists.